Preliminary Trial of Male to Female Sex Reversal by 17β-Estradiol in Combination with Trilostane in Spotted Scat (Scatophagus argus) - Zheng-Ting Jiang; Gang Shi; Dong-Neng Jiang; Yu Li; Yuan-Qing Huang; Hong-Juan Shi; Guang-Li Li (Fishes, 2023)
The spotted scat (Scatophagus argus) is an important ornamental species with sexually biased ornamental values that favor males. Therefore, it makes sense to breed mono-male fingerlings as ornamental fish. The spotted scat has an XX/XY sex determination system; therefore, the first step in producing genetically all-male offspring should be the induction of a fertile sex-reversed XY pseudo-female, which would then be mated with a normal XY male to produce a YY super-male. However, the XY pseudo-female produced by estradiol (E2) treatment failed due to ovarian malformations. Here, male to female sex reversal was induced in spotted scat through a combination of E2 and an androgen inhibitor (trilostane, TR). Spotted scat fingerlings of approximately 2.8–3.5 cm were fed a diet containing both E2 (300 µg/g) and TR (300 µg/g). The fish were treated for 90 days and then fed a normal diet until they reached one year of age, when they were sampled. Twenty-eight treated XY individuals were identified using sex-linked markers. According to their gonadal histological characteristics, these treated XY fish could be divided into three groups: males with testes (n = 21), intersex individuals with ovaries–testes (n = 3), and fully sex-reversed individuals with ovaries (n = 4). All treated XX fish (n = 8) developed into normal females. There were no obvious abnormalities in the ovaries of the XY sex-reversed fish compared to the treated XX fish. Serum 11-ketotestosterone (11-KT) levels were significantly lower in XY-reversed females and treated XX females than in XY males. Compared with XY male fish, the expression of female (42sp50, foxl2, figla, zar1, and zp2) and male (dmrt1, gsdf, amh and cyp11b2) biased genes was up- and down-regulated, respectively, in the gonads of XY-completely sex-reversed fish. Immunohistochemical results indicate that 42Sp50 was expressed in oocytes of XY-partially and completely sex-reversed fish, while strong Gsdf signals were mainly detectable in testicular somatic cells of XY-partially sex-reversed fish and XY male fish. XY females were successfully produced by the combined treatment of E2 and TR in the spotted scat. Their fertility will be tested in the future.